1993
DOI: 10.1007/bf01964427
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of pyrimethamine/sulfadoxine in the prevention of toxoplasmic encephalitis relapses andPneumocystis carinii pneumonia in HIV-infected patients

Abstract: The efficacy and safety of 25 mg pyrimethamine plus 500 mg sulfadoxine given twice a week in preventing relapses of AIDS-related toxoplasmic encephalitis was evaluated in an open study. The 56 HIV-infected patients evaluated had responded to intensive treatment with pyrimethamine/clindamycin prior to starting the present prophylactic regimen. Four patients (7 %) experienced relapse while on pyrimethamine/sulfadoxine. The probability of freedom from relapse was > 90% for 12 months and > 80% for 24 months. Side … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
0

Year Published

1995
1995
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(19 citation statements)
references
References 20 publications
0
19
0
Order By: Relevance
“…There has been no evidence of treatment-induced resistance so far reported that have contributing to a relapse of CT. Few studies have arrived at a solution of how to prevent relapses. Pyrimethamine and sulfadoxine twice a week appears to give promising results for prevention of CT. Allergic reactions are usually mild and disappear on continuation, but may limit the value of this regimen (Ruf et al, 1993). Daily doses of pyrimethamine and sulfadiazine are more effective as maintenance therapy for preventing relapses of CT (4.4 compared to 19.5 per 100 patient-years; incidence rate ration, 4.36; p=0.024) than twice weekly administration (Podzamczer et al, 1995).…”
Section: Anti-toxoplasma Therapymentioning
confidence: 99%
“…There has been no evidence of treatment-induced resistance so far reported that have contributing to a relapse of CT. Few studies have arrived at a solution of how to prevent relapses. Pyrimethamine and sulfadoxine twice a week appears to give promising results for prevention of CT. Allergic reactions are usually mild and disappear on continuation, but may limit the value of this regimen (Ruf et al, 1993). Daily doses of pyrimethamine and sulfadiazine are more effective as maintenance therapy for preventing relapses of CT (4.4 compared to 19.5 per 100 patient-years; incidence rate ration, 4.36; p=0.024) than twice weekly administration (Podzamczer et al, 1995).…”
Section: Anti-toxoplasma Therapymentioning
confidence: 99%
“…Standard treatment of toxoplasmosis, on the other hand, utilizes the combination pyrimethamine-sulfadiazine (24). Newer drug combinations which have shown promise for prophylaxis or treatment include pyrimethamine-sulfadoxine (42), trimethoprim-dapsone (23), clindamycin-primaquine (41), and pyrimethamine-clindamycin (19). Atovaquone (566C80), an antimalarial hydroxyquinone with a mechanism of action unlike that of any of the above drugs, has also recently been reported to have significant activity in laboratory animals (14) and humans (15).…”
mentioning
confidence: 99%
“…Twenty reported findings from studies that were performed up to 1996 ( n = 1,228) (Table 1) [34−51], and six described results of studies performed after 1996 ( n = 368) (Table 2) [52−57]. …”
Section: Resultsmentioning
confidence: 99%
“…Most studies co-administered folinic acid (leucovorin) with pyrimethamine for acute therapy; only four did not report co-administering folinic acid with pyrimethamine – three in the pre-HAART group [35,58,59] and one in the post-HAART group [52]. Of the included studies, 11 did not report co-administering folinic acid with pyrimethamine during maintenance therapy [34,35,38,41,45,47,49,51,52,54,60]. …”
Section: Resultsmentioning
confidence: 99%